Protective effect of rhubarb on the intestinal mucosal barrier - Chen, De-Chang (World J Gastroenterol, 1997)
AIM: To investigate the mechanism of rhubarb protection of the gut barrier. METHODS: The gut barrier damage models caused by hemorrhagic shock and intraperitoneal endotoxin were used to study the protective effect of rhubarb on the intestinal mucosal barrier. Rats were randomly divided into four groups, as follows: treatment (rhubarb) group; Positive control group; Negative control group; Placebo treatment group. Plasma endotoxin, tissue superoxidedismutase (SOD) and lipoperoxide (LPO) concentrations were measured and histological analysis was performed. Rhubarb was observed to have a protective effect on the gut. RESULTS: Rhubarb decreased intestinal permeability, attenuated endotoxin absorption (endotoxin serum levels: shock group 0.557 EU/mL ± 0.069 EU/mL vs rhubarb group 0.345 EU/mL ± 0.055 EU/mL), and decreased tissue SOD and tissue LPO levels (SOD serum, intestine and liver levels: endotoxin group 122.92 NU/mL ± 43.19 NU/mL, 292.24 NU/mL ± 88.76 NU/mL, 272.70 NU/mL ± 85.79 NU/mL vs rhubarb group 312.23 NU/mL ± 54.93 NU/mL, 391.09 NU/mg ± 98.16 NU/mg, 542.86 NU/mg ± 119.93 NU/mg; LPO content in the intestine and liver: endotoxin group 8.57 μmol/L ± 2.58 μmol/L, 86.97 μmol/L ± 46.54 μmol/L vs rhubarb group 3.05 μmol/L ± 1.13 μmol/L, 13.18 μmol/L ± 19.64 μmol/L). Gut histopathology revealed that rhubarb promoted goblet cell proliferation, increased mucus secretion and protected intestinal mucosa in the hemorrhagic shock model. CONCLUSION: Rhubarb may protect the gut barrier by decreasing intestinal permeability, scavenging oxygen free radicals, and promoting goblet cell proliferation within the intestinal mucosa.